Recovering endothelial function - Bryce Moncloa, Alfonso (2014)
Atherosclerosis starts early in life. The presence of risk factors like hypertension, smoking, dyslipidemia and diabetes as well as obesity and metabolic syndrome accelerates its progress. These factors generate endothelial dysfunction, oxidative stress and inflammation, with early appearance of foamy cells, fatty streaks and atheromatous plaques. These plaques are vulnerable to erosion and rupture, the so called atherothrombotic phenomenon, leading to acute vascular events like acute coronary or cerebrovascular syndromes. Managing and treating the metabolic syndrome, early markers of cardiovascular risk, could slow down end organ aging and damage, probably without reduction of mortality but focusing on three fundamental aspects of early detection of subclinical atherothrombosis: prevention of cardiovascular events, protection of end organs, and improvement of quality of life.